2006
DOI: 10.1007/s10886-006-9200-2
|View full text |Cite
|
Sign up to set email alerts
|

Response to Host Volatiles by Native and Introduced Populations of Dendroctonus valens (Coleoptera: Curculionidae, Scolytinae) in North America and China

Abstract: Bark beetles (Coleoptera: Curculionidae, Scolytinae) have specialized feeding habits, and commonly colonize only one or a few closely related host genera in their geographical ranges. The red turpentine beetle, Dendroctonus valens LeConte, has a broad geographic distribution in North America and exploits volatile cues from a wide variety of pines in selecting hosts. Semiochemicals have been investigated for D. valens in North America and in its introduced range in China, yielding apparent regional differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 49 publications
1
75
0
Order By: Relevance
“…EAG experiments on D. valens to monoterpene revealed that (-)-b-pinene was the most potent compound tested ; however, this was not wholly consistent with the field and laboratory behavior research where (? )-3-carene was confirmed to be the most effective lure among all the terpenes, but EAG results were lower than for (-)-bpinene Sun et al 2004;Erbilgin et al 2007;Zhang et al 2009). …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…EAG experiments on D. valens to monoterpene revealed that (-)-b-pinene was the most potent compound tested ; however, this was not wholly consistent with the field and laboratory behavior research where (? )-3-carene was confirmed to be the most effective lure among all the terpenes, but EAG results were lower than for (-)-bpinene Sun et al 2004;Erbilgin et al 2007;Zhang et al 2009). …”
Section: Discussionmentioning
confidence: 81%
“…These play an important role in the host selection behavior of some conifer bark beetles, either as attractive kairomones or aggregation pheromone co-attractants (Erbilgin and Raffa 2000;Byers 2004;Seybold et al 2006). An example is, when bark beetles are attracted to aggregate at a Tomicus piniperda tree, the tree releases a kairomone mixture of three EAD-active monoterpenes: a-pinene, 3-carene and terpinolene (Byers et al 1985;Schlyter et al 2000) and a-and b-pinene, and 3-carene in D. valens Erbilgin et al 2007). Myrcene is a kairomone for the mountain pine beetle, Dendroctonus ponderosae Hopkins (Billings et al 1976;Conn et al 1983;Libbey et al 1985;Borden et al 1987), and b-phellandrene increases the attraction of the pine engraver, Ips pini (Say), to its aggregation pheromone, ipsdienol (Miller and Borden 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that 3-carene is the most efficient attractant for RTB in China and the United States (Sun et al 2004, Erbilgin et al 2007). Here, we have shown that adult RTB was significantly more attracted to the amounts of 3-carene induced by Chinese distinct genotype (CRDG group) than to levels induced by other fungal groups in the laboratory (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because the exact relationship between the spruce bark beetle and most host terpenoids is unknown it is difficult to predict accurately how qualitative differences in terpene chemistry will affect beetle colonization biology (Erbilgin et al 2007b). However, four of the most abundant constitutive compounds in all spruce species [(-)-α-pinene, ß-pinene, ß-phellandrene, myrcene] elicit strong antennal responses in the spruce bark beetle and are probably important in the host selection process (Andersson et al 2009;Kalinova et al 2014).…”
Section: The Concentration Of Individual Terpenoids In Constitutive Bmentioning
confidence: 99%